QoS-Aware Web-Services Ranking: Normalization Techniques Comparative Analysis For LSP Method - Polska, Olga; Jamil Alsayaydeh, Jamil Abedalrahim; Shkarupylo, Vadym (Asian Research Publishing Network (ARPN), 2021)
Service-oriented architecture (SOA) and Internet services technologies offer advanced solutions for creating distributed business processes and applications. At the same time, services must be available to a growing number of users and satisfy their requirements for both functional and non-functional properties of services. The problem of services selection based on the quality of services is formulated as a multi-criteria decision-making (MCDM) problem. MCDM methods typically require preliminary normalization of the criteria, which in turn can significantly affect the results of multi-criteria problem resolving. In this paper, the effects of commonly known normalization techniques (MAX-MIN, VECTOR, MAX, SUM and LOG) on the ranking Web services using a method of Logic Scoring of Preference (LSP) are investigated. As an outcome of study conducted, the approach to the usage of the Vector, Sum and Max techniques to normalize the criteria when applying the LSP method has been proposed